Epstein - Barr virus infection is associated with the nuclear factor - kappa B p65 signaling pathway in renal cell carcinoma - Farhadi, Ali; Namdari, Sepide; Chong, Pei Pei; Geramizadeh, Bita; Behzad‑Behbahani, Abbas; Sekawi, Zamberi; Sharifzadeh, Sedigheh (BioMed Central, 2022)
Background: There have been few studies regarding viral involvement in the pathogenesis of renal cell carcinoma (RCC). The aim of this study was to examine the possible association of Epstein–Barr virus (EBV) infection with clinicopathological features and cellular biomarkers including p53, p16INK4a, Ki-67 and nuclear factor-kappa B (NF-κB) in RCC tumors. Methods: In this prospective study, 122 histologically confirmed Formalin-fixed Paraffin-embedded RCC tissue specimens along with 96 specimens of their corresponding peritumoral tissues and 23 samples of blunt renal injuries were subjected to nested polymerase chain reaction (nPCR) in order to amplify EBV DNA sequences. The expression of p53, p16INK4a, Ki-67 and NF-κB was investigated by immunohistochemistry (IHC) assay. Statistical analysis was employed to demonstrate the possible associations. Results: Infection with EBV was found to be significantly associated with RCC. Our results indicate that p65 NF-κB signaling pathway is probably involved in EBV-mediated RCC pathogenesis. Moreover, we found p53, Ki-67 and cytoplasmic NF-κB expression to be associated with tumor nuclear grade in RCC patients. The expression of p53 and Ki-67 was associated with primary tumor category as well. In addition, p53 overexpression was significantly more frequent among nonconventional RCC tumors than the conventional histologic type. Conclusions: Infection with EBV is likely to play an important role in the development of RCC through the constitutive and permanent activation of NF-κB p65 signaling pathway. However, more experiments and supporting data are required to reach a decisive conclusion.